Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acs.langmuir.9b02101
|View full text |Cite
|
Sign up to set email alerts
|

Nanodomain Formation in Planar Supported Lipid Bilayers Composed of Fluid and Polymerized Dienoyl Lipids

Abstract: Polymerization of synthetic phospholipid monomers has been widely used to enhance the stability of lipid membranes in applications such as membrane-based biosensing, where the inherent instability of fluid-phase lipid bilayers can be problematic. However, lipid polymerization typically decreases membrane fluidity, which may be required to maintain the activity of reconstituted integral proteins and peptides. Prior work has shown that a bilayer composed of binary mixtures of poly(lipid) and fluid lipid exhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 55 publications
4
22
0
Order By: Relevance
“…The poly­(bis-SorbPC) domains are irregularly shaped islands, with areas of 3000–6000 nm 2 , and the DPhPC domains are somewhat larger. The height difference between the domains, 0.3–0.4 nm, indicates that the lipids in the upper and lower leaflets of the bilayer are mostly in registry . The present study extends the previous publication.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…The poly­(bis-SorbPC) domains are irregularly shaped islands, with areas of 3000–6000 nm 2 , and the DPhPC domains are somewhat larger. The height difference between the domains, 0.3–0.4 nm, indicates that the lipids in the upper and lower leaflets of the bilayer are mostly in registry . The present study extends the previous publication.…”
Section: Introductionsupporting
confidence: 87%
“…Binary planar supported lipid bilayers (PSLBs) composed of 1,2-diphytanoyl- sn -glycero-3-phosphocholine (DPhPC), a fluid-phase lipid, and 1,2-bis­[10-(2′,4′-hexadienoloxy)­decanoyl]- sn -glycero-3-phosphocholine (bis-SorbPC), a polymerizable lipid are the subject of the present study (the molecular structures are shown in Figure S1). In a previous publication, we showed that polymerization of DPhPC/bis-SorbPC PSLBs induces phase segregation, resulting in the formation of subμm domains composed predominately of poly­(bis-SorbPC) surrounded by a semicontinuous phase composed predominately of DPhPC; a typical AFM image is shown in Figure . The poly­(bis-SorbPC) domains are irregularly shaped islands, with areas of 3000–6000 nm 2 , and the DPhPC domains are somewhat larger.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…SLBs can be readily assembled on solid surfaces by a number of convenient methods from liposome fusion, Langmuir–Blodgett–Schaeffer transfer, or solvent-assisted lipid bilayer formation . Due to their planar geometry, SLBs are compatible with various surface-sensitive characterization and analytical tools, including quartz crystal microbalance with dissipation (QCM-D), , surface plasmon resonance, atomic force microscopy, ,, electrochemical impedance spectroscopy, , and fluorescence microscopy . The stability of SLBs (owing to the solid support) and their compatibility with various analytical techniques make them popular and convenient model biomembrane surfaces. , …”
Section: Introductionmentioning
confidence: 99%